Critical Review—Recent Progress in NIR Fluorophores Emitting over 1000 nm for Bioimaging. (1st January 2019) - Jin, Takashi
Abstract : During the last five years, significant advances have been made in the synthesis of near-infrared (NIR) fluorophores emitting over 1000 nm for non-invasive deep-tissue imaging. Nano-materials such as single-walled carbon nanotubes (SWCNTs), following Ag2 S and PbS quantum dots (QDs) have been employed as the first-generation NIR fluorescent probes, by which superior capabilities of NIR fluorescence imaging at the wavelengths of 1000–1400 nm (second NIR window) have been demonstrated. Recently, from the viewpoint of biomedical applications, organic-dye based NIR fluorophores emitting beyond 1000 nm have been synthesized. In this short review, we focus on recent advances in nanomaterial and organic-dye based NIR fluorophores for intravital deep bioimaging in the second NIR window.